O impacto das políticas neoliberais na gestão democrática da Rede Estadual de Ensino de Mato Grosso - Abich, Luzia Pereira de Souza (2005)
The objective of this work was to analyze the impacts of the neoliberal politics in the democratic management of the public net of education. The research happened at two moments, being that in the first one, I made a thematic bibliography that it included beyond already fulfilled researches and analyses, documents published by Seduc/MT and lines of direction and the researches of field in a public school, to perceive the concrete difficulties evidenced by the process of democratization of the management, with the installation of the enterprise model adopted by the Seduc/MT. It was possible to perceive, through this work that the retaken one of the democratic management in the state net of education, if gave in the confrontation of two forces antagonistic politics, or either, on one hand the government of the State, with neoliberais apparatus, and on the other hand, the pressure of the movement of educators in the direction to hinder the advance them neoglobalizantes orientations in the politics for the education in the State. The study it disclosed that parallel to the instant where the school theoretically received autonomy, in the practical one, a characteristic model of management presenting enterprise was tax, becoming incompatible with the process of democratization in course, based in the theory. The attempt to lead the school being based on enterprise principles, exactly with a new roupagem caused unfoldings with funestas consequences for the pedagogical autonomy of searched school e, consequently for the democratization of its management that characterize itself in the increase of the bureaucracy, in the elaboration mechanic documents to only take care like requirement of the central agency, in the method of clipping of the participation, the inhibition of the practical of reflection, for times truculenta, in the relation school/Seduc.